Light gasoline cracking yield-increasing propylene catalyst containing porous vermiculite-containing silica gel mesoporous composite material as well as preparation method and application of light gasoline cracking yield-increasing propylene catalyst

By introducing porous vermiculite-containing silica mesoporous composite material into the light gasoline catalytic cracking catalyst, the problems of low selectivity and poor stability of propylene in the existing catalyst are solved, and the effect of improving the conversion rate of olefins and propylene selectivity is achieved.

CN119869603AActive Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311378145.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25
Estimated Expiration
2043-10-23

AI Technical Summary

Technical Problem

The propylene of the existing light gasoline catalytic cracking catalyst has low selectivity and poor stability, resulting in a reduced selectivity of the target product propylene.

Method used

A light gasoline cracking and increasing production propylene catalyst containing porous vermiculite-containing silica mesoporous composite material is used. The catalyst consists of hydrogen-type high-silicon ZSM-5 zeolite molecular sieve, porous vermiculite-containing silica mesoporous composite material, bonded oxide and modified oxide. The performance of the catalyst is improved through specific preparation methods and component ratios.

Benefits of technology

The conversion rate of olefins and the selectivity of propylene in light gasoline are significantly improved, while the stability of the catalyst is enhanced and side reactions are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869603A_ABST
    Figure CN119869603A_ABST
Patent Text Reader

Abstract

The invention relates to the field of petrochemical industry, and discloses a light gasoline cracking yield-increasing propylene catalyst containing a porous vermiculite-containing silica gel mesoporous composite material, and a preparation method and application thereof. The catalyst comprises a zeolite molecular sieve, a porous vermiculite-containing silica gel mesoporous composite material, a bonding oxide and a modified oxide, and based on the total weight of the catalyst, the catalyst comprises 45-65 wt% of the zeolite molecular sieve, 15-35 wt% of the porous vermiculite-containing silica gel mesoporous composite material, 10-20 wt% of the bonding oxide and 1-9 wt% of the modified oxide; the average particle size of the porous vermiculite-containing silica gel mesoporous composite material is 20-60 [mu] m, the specific surface area is 100-800 m < 2 > / g, the pore volume is 1-2 mL / g, the pore diameter is in four-peak distribution, and the first most probable pore diameters corresponding to four peaks are 1-2 nm, 2-3 nm, 3-5 nm and 20-40 nm respectively; when the catalyst is used for light gasoline catalytic cracking reaction, not only can propylene be obtained, but also the olefin content of a light gasoline product can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of petrochemical industry, and in particular to a catalyst for increasing propylene production by cracking light gasoline containing a porous vermiculite-containing silica gel mesoporous composite material, and a preparation method and application thereof. Background Art

[0002] Propylene is a very important organic chemical raw material. With the growing demand for propylene downstream products (including polypropylene, acrylic acid, and acrylonitrile), the demand for propylene is also increasing year by year. So far, my country's propylene is still in short supply, and the traditional ethylene co-production and refinery propylene recovery methods are increasingly unable to meet market demand.

[0003] The catalyst used in the catalytic cracking of light gasoline to increase propylene production is mainly a zeolite molecular sieve catalyst. Compared with metal oxides, zeolite molecular sieves have the advantages of orderly pore structure, large specific surface area, and adjustable number of acidic centers and acid strength. Therefore, most researchers focus on zeolite molecular sieve catalysts. The main components of the light gasoline catalytic cracking catalysts involved in the prior art are ZSM-5 molecular sieve, ZSM-11 molecular sieve, ZRP molecular sieve or ZSM-35 molecular sieve. The results show that the pore structure, surface acidity and structural stability of the catalyst are the key factors affecting the catalytic cracking of olefins. Unmodified acidic ZSM-5 molecular sieve has good initial activity in the light gasoline cracking reaction, but poor stability. In order to improve the performance of the catalyst, many researchers have conducted in-depth research on the synthesis and modification of zeolite molecular sieves.

[0004] The light gasoline catalytic cracking catalyst disclosed in the prior art has zeolite molecular sieve or modified zeolite molecular sieve as the main component. Since zeolite molecular sieve is a microporous molecular sieve with narrow pore structure, it is easy to cause side reactions, thereby reducing the selectivity of the target product propylene.

[0005] Therefore, the propylene selectivity of the catalyst for increasing propylene production by catalytic cracking of light gasoline in the prior art needs to be further improved. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects of low propylene yield and poor stability of the light gasoline catalytic cracking and propylene production increasing catalyst in the prior art, and to provide a light gasoline cracking and propylene production increasing catalyst containing a porous vermiculite-containing silica gel mesoporous composite material and a preparation method and application thereof. The catalyst provided by the present invention is used for the catalytic cracking reaction of light gasoline, which can not only obtain propylene but also reduce the olefin content of the light gasoline product.

[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a catalyst for increasing propylene production by cracking light gasoline, wherein the catalyst for increasing propylene production by cracking light gasoline comprises a zeolite molecular sieve, a porous vermiculite-containing silica gel mesoporous composite material, a bonding oxide and a modified oxide, and based on the total weight of the catalyst for increasing propylene production by cracking light gasoline, the content of the zeolite molecular sieve is 45-65% by weight, the content of the porous vermiculite-containing silica gel mesoporous composite material is 15-35% by weight, the content of the bonding oxide is 10-20% by weight, and the content of the modified oxide is 1-9% by weight;

[0008] The average particle size of the porous vermiculite-containing silica gel mesoporous composite material is 20-60 μm, and the specific surface area is 100-800 m 2 / g, the pore volume is 1-2mL / g, the pore size presents a four-peak distribution, and the first most probable pore size corresponding to the four peaks is 1-2nm, the second most probable pore size is 2-3nm, the third most probable pore size is 3-5nm, and the fourth most probable pore size is 20-40nm.

[0009] The second aspect of the present invention provides a method for preparing the above-mentioned catalyst for increasing propylene production by cracking light gasoline, wherein the preparation method comprises:

[0010] (1) in the presence of dilute nitric acid, mixing a zeolite molecular sieve, a porous vermiculite-containing silica gel mesoporous composite material, a binder and an extrusion aid, extruding and performing a first calcination treatment to obtain a catalyst precursor;

[0011] (2) The catalyst precursor is immersed in an aqueous solution of a modified oxide precursor and then dried and subjected to a second calcination treatment to obtain a catalyst for increasing propylene production by cracking light gasoline.

[0012] The third aspect of the present invention provides an application of the above-mentioned catalyst for increasing propylene production by cracking light gasoline in catalytic cracking.

[0013] Through the above technical solution, the technical solution of the present invention has the following advantages:

[0014] (1) The main components of the light gasoline cracking catalyst provided by the present invention are hydrogen-type high-silicon ZSM-5 zeolite molecular sieve and porous vermiculite-containing silica gel mesoporous composite material. The raw material price is low and the preparation method is simple.

[0015] (2) The catalyst for increasing propylene production by cracking light gasoline provided by the present invention is used in the light gasoline cracking reaction, which can not only effectively improve the conversion rate of olefins in light gasoline and the selectivity of target product propylene, but also effectively reduce the olefin content in light gasoline.

[0016] (3) The method for preparing the catalyst for increasing propylene production by cracking light gasoline of the present invention has a simple process, easy-to-control conditions and good product repeatability.

[0017] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.

[0019] Figure 1 is the X-ray diffraction pattern of the porous vermiculite-containing silica gel mesoporous composite material A prepared in Example 1 of the present invention;

[0020] Figure 2 This is a SEM scanning electron microscope image of the porous vermiculite-containing silica gel mesoporous composite material A prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0022] The first aspect of the present invention provides a catalyst for increasing propylene production by cracking light gasoline, wherein the catalyst for increasing propylene production by cracking light gasoline comprises a zeolite molecular sieve, a porous vermiculite-containing silica gel mesoporous composite material, a bonding oxide and a modified oxide, and based on the total weight of the catalyst for increasing propylene production by cracking light gasoline, the content of the zeolite molecular sieve is 45-65% by weight, the content of the porous vermiculite-containing silica gel mesoporous composite material is 15-35% by weight, the content of the bonding oxide is 10-20% by weight, and the content of the modified oxide is 1-9% by weight;

[0023] The average particle size of the porous vermiculite-containing silica gel mesoporous composite material is 20-60 μm, and the specific surface area is 100-800 m 2 / g, the pore volume is 1-2mL / g, the pore size presents a four-peak distribution, and the first most probable pore size corresponding to the four peaks is 1-2nm, the second most probable pore size is 2-3nm, the third most probable pore size is 3-5nm, and the fourth most probable pore size is 20-40nm.

[0024] The inventors of the present invention have found that the main components of the light gasoline cracking catalysts disclosed in the prior art are all microporous zeolite molecular sieves (including ZSM-5, ZSM-11, ZSM-35 or ZRP). Although the microporous molecular sieve has an orderly and stable structure, the pore size is relatively narrow, generally between 0.4-0.7nm. During the olefin cracking reaction, it is difficult for the larger reactant molecules and product molecules to diffuse between the narrow pores, which not only affects the contact between the reactants and the active center, but also easily leads to the occurrence of side reactions such as deep dehydrogenation.

[0025] The inventors of the present invention found in the preparation research of light gasoline cracking catalyst that if a certain amount of porous vermiculite-containing silica gel mesoporous composite material is mixed and modified with hydrogen-type high-silicon ZSM-5 molecular sieve, and used as the main component of the catalyst for light gasoline catalytic cracking reaction, not only can the propylene selectivity be effectively improved, but also the conversion rate of olefins in light gasoline can be increased. Compared with the HZSM-5 molecular sieve with narrow pores, the porous vermiculite-containing silica gel mesoporous composite material has four pore structures with different sizes (respectively 1-2nm, 2-3nm, 3-5nm and 20-40nm). Mixing an appropriate amount of porous vermiculite-containing silica gel mesoporous composite material with ZSM-5 molecular sieve is conducive to the smooth diffusion of reactant molecules and product molecules with larger molecular volume, and the occurrence of side reactions can be effectively avoided.

[0026] According to the present invention, preferably, the specific surface area of ​​the porous vermiculite-containing silica gel mesoporous composite material is 100-200m 2 / g, and the specific surface area is more preferably 104-168m 2 / g, pore volume is 1.4-1.8mL / g, pore size is four-peak distribution, and the first most probable pore size corresponding to the four peaks is 1.2-1.9nm, the second most probable pore size is 2.6-2.7nm, the third most probable pore size is 3.5-3.9nm, and the fourth most probable pore size is 31-37nm. Under this condition, it is more conducive to the diffusion of raw material molecules and product molecules in the reaction, and more effectively inhibits the occurrence of side reactions caused by the narrow pores of the zeolite molecular sieve.

[0027] According to the present invention, based on the total weight of the catalyst for increasing propylene production by cracking light gasoline, the content of the zeolite molecular sieve is 51-58% by weight, the content of the porous vermiculite-containing silica gel mesoporous composite material is 23-28% by weight, the content of the adhesive oxide is 11-19% by weight, and the content of the modified oxide is 3-7% by weight. By controlling the content of each component in the catalyst provided by the present invention within this range, the olefin conversion rate in light gasoline and the selectivity of propylene can be effectively improved.

[0028] In the present invention, it should be noted that, based on the total weight of the light gasoline cracking and propylene production increasing catalyst, the total content of the zeolite molecular sieve, the porous vermiculite-containing silica gel mesoporous composite material, the bonding oxide and the modified oxide is 100%.

[0029] According to the present invention, the zeolite molecular sieve is a hydrogen-type high-silicon ZSM-5 molecular sieve; preferably, the SiO2 / Al2O3 molar ratio of the hydrogen-type high-silicon ZSM-5 molecular sieve is 100-800, more preferably 200-500, and further preferably 200-300.

[0030] According to the present invention, the weight ratio of the hydrogen-type high-silicon ZSM-5 molecular sieve to the porous vermiculite-containing silica gel mesoporous composite material is (1.5-4.5):1, preferably (2-4):1, and more preferably (2.2-3.76):1.

[0031] According to the present invention, the adhesive oxide is a product of calcining an adhesive, preferably silicon oxide and / or aluminum oxide; more preferably, the adhesive is selected from one or more of silica sol, aluminum sol, pseudo-boehmite and diaspore.

[0032] According to the present invention, the modified oxide is selected from one or more of magnesium oxide, calcium oxide, strontium oxide, barium oxide, zinc oxide, boron oxide, cerium oxide, lanthanum oxide, zirconium dioxide and phosphorus-containing oxides.

[0033] According to the present invention, the method for preparing the porous vermiculite-containing silica gel mesoporous composite material comprises:

[0034] (a) in the presence of a first template, a second template, trimethylpentane and ethanol, tetramethoxysilane is first contacted with an acidic aqueous solution, and the mixture after the first contact is crystallized, washed and filtered to obtain a mesoporous molecular sieve filter cake 1;

[0035] (b) subjecting the third template, tetraethyl orthosilicate and aqueous ammonia to a second contact, and subjecting the mixture after the second contact to crystallization and filtering to obtain a mesoporous molecular sieve filter cake 2;

[0036] (c) contacting water glass, an inorganic acid and n-butanol for a third time, and filtering the mixture after the third contact to obtain a silica gel filter cake;

[0037] (d) The mesoporous molecular sieve material filter cake 1, the mesoporous molecular sieve material filter cake 2, vermiculite, and the silica gel filter cake are mixed and ball-milled, and the solid powder after the ball milling is slurried with water to obtain a slurry, and the slurry is spray-dried and calcined to obtain a porous vermiculite-containing silica gel mesoporous composite material.

[0038] According to the present invention, in step (a), the first template and the second template are triblock copolymers of polyethylene oxide-polypropylene oxide-polyethylene oxide; preferably, the first template is P123, and the second template is F127; the first template is P123 (molecular formula is EO 20 PO 70 EO 20 ), the second template is F127 (molecular formula is EO 106 PO 70 EO 106 ).

[0039] According to the present invention, the pH value of the acidic aqueous solution is 1-6, preferably, the pH is 3-5; more preferably, the acidic aqueous solution is a 1-5 mol / L acetic acid and sodium acetate buffer solution.

[0040] According to the present invention, the molar ratio of the first template, the second template, ethanol, the acidic aqueous solution, trimethylpentane and tetramethoxysilane is 1: (0.1-2): (100-500): (150-900): (200-500): (50-200), preferably 1: (0.2-1): (200-400): (300-600): (250-400): (70-150).

[0041] According to the present invention, the conditions for the first contact include: a temperature of 10-40° C. and a time of 10-48 h.

[0042] According to the present invention, in step (a), the crystallization conditions include: temperature of 30-80° C. and time of 10-48 h.

[0043] According to the present invention, in step (a), the washing conditions are not particularly limited. For example, the washing process may include: obtaining a solid product after filtration, repeatedly washing the solid product with distilled water (the number of washing times may be 2-10) and then filtering.

[0044] According to the present invention, the suction filtration separation is a method of separating liquid and solid particles well known to those skilled in the art, which utilizes air pressure to separate liquid and solid particles or a mixture of liquid and liquid.

[0045] According to the present invention, in step (b), the third template is hexadecyltrimethylammonium bromide.

[0046] According to the present invention, the molar ratio of the tetraethyl orthosilicate, the third template, the ammonia in the ammonia water and the water in the ammonia water is 1: (0.1-1): (0.1-5): (100-200), preferably 1: (0.2-0.5): (1.5-3.5): (120-180).

[0047] According to the present invention, the conditions for the second contact include: temperature of 10-60° C. and time of 1-5 h.

[0048] According to the present invention, in step (c), the inorganic acid is selected from one or more of sulfuric acid, nitric acid and hydrochloric acid; preferably, the weight ratio of the inorganic acid: n-butanol: water glass is 1: (0.5-2): (3-6).

[0049] According to the present invention, the third contact conditions include: temperature of 10-60°C, time of 1-5h, and pH value of 2-4.

[0050] According to the present invention, in step (d), based on 100 parts by weight of the mesoporous molecular sieve filter cake 1, the amount of the mesoporous molecular sieve filter cake 2 is 20-300 parts by weight, preferably 50-200 parts by weight; the amount of the silica gel filter cake is 50-500 parts by weight, preferably 100-300 parts by weight; the amount of the vermiculite is 50-500 parts by weight, preferably 100-300 parts by weight.

[0051] According to the present invention, in step (d), the ball milling implementation method is as follows: add mesoporous molecular sieve filter cake 1, mesoporous molecular sieve filter cake 2, vermiculite and silica gel filter cake into a ball mill of a ball mill, the inner wall of the ball mill is agate, the diameter of the grinding ball is 2-3mm, and the rotation speed is 300-500r / min. Grind continuously for 2-50 hours at a temperature of 20-100°C in the ball mill, and then take out the solid powder. The number of grinding balls depends on the size of the ball mill. For a ball mill of 50-150mL, one grinding ball can be used. The material of the grinding ball is agate.

[0052] According to the present invention, in step (d), the spray drying conditions include: temperature 150-220° C., rotation speed 10000-15000 r / min.

[0053] According to the present invention, in step (d), the calcination conditions include: the temperature can be 400-600° C., preferably 450-550° C.; the time can be 10-60 h, preferably 20-30 h.

[0054] The second aspect of the present invention provides a method for preparing the above-mentioned catalyst for increasing propylene production by cracking light gasoline, wherein the preparation method comprises:

[0055] (1) in the presence of dilute nitric acid, mixing a zeolite molecular sieve, a porous vermiculite-containing silica gel mesoporous composite material, a binder and an extrusion aid, extruding and performing a first calcination treatment to obtain a catalyst precursor;

[0056] (2) The catalyst precursor is immersed in an aqueous solution of a modified oxide precursor and then dried and subjected to a second calcination treatment to obtain a catalyst for increasing propylene production by cracking light gasoline.

[0057] According to the present invention, in step (1), relative to 500 mL of dilute nitric acid, the amount of the zeolite molecular sieve is 1000-1400 parts by weight, the amount of the porous vermiculite-containing silica gel mesoporous composite material is 400-600 parts by weight, the amount of the adhesive is 300-500 parts by weight, and the amount of the extrusion aid is 100-300 parts by weight; preferably, relative to 500 mL of dilute nitric acid, the amount of the zeolite molecular sieve is 1100-1200 parts by weight, the amount of the porous vermiculite-containing silica gel mesoporous composite material is 500-550 parts by weight, the amount of the adhesive is 350-400 parts by weight, and the amount of the extrusion aid is 150-200 parts by weight.

[0058] According to the present invention, in step (2), the amount of the catalyst precursor is 70-100 parts by weight, and the amount of the oxide precursor is 10-30 parts by weight relative to 100 mL of water; preferably, the amount of the catalyst precursor is 95-100 parts by weight, and the amount of the oxide precursor is 10-20 parts by weight relative to 100 mL of water.

[0059] According to the present invention, the modified oxide precursor comprises an inorganic salt of a metal and / or an inorganic acid of a non-metal; preferably, the metal is selected from one or more of magnesium, calcium, strontium, barium, zinc, cerium, lanthanum and zirconium, and the non-metal is boron and / or phosphorus;

[0060] According to the present invention, the extrusion aid is selected from one or more of sesbania powder, cellulose, polyethylene glycol, polyvinyl alcohol and starch, more preferably sesbania powder and / or polyethylene glycol.

[0061] According to the present invention, in step (1), the conditions for the first calcination include: a temperature of 500-600° C. and a time of 3-20 h.

[0062] According to the present invention, in step (1), the drying conditions include: temperature of 70-160° C. and time of 4-10 h.

[0063] According to the present invention, in step (2), the conditions for the second calcination include: a temperature of 500-600° C. and a time of 4-10 h.

[0064] According to the present invention, in step (2), the drying conditions include: temperature of 60-120° C. and time of 5-20 h.

[0065] The third aspect of the present invention provides an application of the above-mentioned catalyst for increasing propylene production by cracking light gasoline in catalytic cracking.

[0066] According to the present invention, the specific operation of the application is as follows: at a temperature of 450-580°C, a pressure of 0.01-0.5 MPa and a weight hourly space velocity of 1-30 h -1 Under the conditions of , a raw material containing light gasoline is contacted with a light gasoline cracking catalyst for increasing propylene production in a fixed bed adiabatic reactor to generate a reaction mixture containing propylene and ethylene. Propylene is obtained through heat exchange, cooling and separation, and the separated ethylene and lighter components are returned to the reactor.

[0067] In the present invention, a method for applying a catalyst for increasing propylene production by cracking light gasoline is provided, wherein the light gasoline raw material can be selected from:

[0068] (1) Light gasoline fraction obtained from a catalytic cracking unit;

[0069] (2) The C5+ fraction of methanol to olefins.

[0070] The method provided by the present invention can be used as a separate method for preparing propylene, and can also be used in combination with an FCC unit or a methanol to olefins unit in an oil refinery.

[0071] The characteristics of microporous zeolite molecular sieve catalysts with relatively low silicon-aluminum ratios used in the catalytic cracking reaction of light gasoline are fast reaction speed, poor propylene selectivity and short service life. Relatively speaking, high silicon-aluminum ratio zeolite molecular sieve catalysts with the addition of modifying components have certain improvements in propylene selectivity and stability, but are still prone to secondary reactions during the reaction process. The light gasoline cracking and propylene production increasing catalyst provided by the present invention adopts a mixture of a hydrogen-type high silicon-aluminum ratio ZSM-5 zeolite molecular sieve and a porous vermiculite-containing silica gel mesoporous composite material as the main active component, and introduces an appropriate amount of oxide as a modifying component, which can significantly improve the conversion rate of olefins in light gasoline, the selectivity of propylene and the stability of the catalyst.

[0072] The present invention will be described in detail below through examples.

[0073] In the following examples and comparative examples:

[0074] The X-ray diffraction analysis of the samples was carried out on an X-ray diffractometer model D8Advance purchased from Bruker AXS, Germany; the pore structure parameter analysis of the samples was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics, USA. The samples were vacuum degassed at 350°C for 4 hours before measurement, and the sample specific surface area was calculated using the BET method, and the pore volume was calculated using the BJH model; the SEM scanning electron microscope images of the samples were obtained on an XL-30 field emission environmental scanning electron microscope produced by FEI, USA; the elemental analysis experiment of the catalyst samples was carried out on an EagleⅢ energy dispersive X-ray fluorescence spectrometer produced by EDAX, USA.

[0075] The drying oven was produced by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9030A.

[0076] The muffle furnace is produced by CARBOLITE, model CWF1100.

[0077] The polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymers P123 and F127 used in the examples and comparative examples were purchased from Aldrich; ZSM-5 molecular sieves with different silicon-aluminum ratios were purchased from Shanghai Fuxu Molecular Sieve Co., Ltd.; aluminum sol was purchased from Zibo Jiarun Chemical Co., Ltd.; and pseudo-boehmite was purchased from Zibo Hengqi Powder New Material Co., Ltd.

[0078] Other reagents used in the examples and comparative examples were purchased from Sinopharm Chemical Reagent Co., Ltd. and were of analytical purity.

[0079] Example 1

[0080] This example is intended to illustrate the catalyst for increasing propylene production by cracking light gasoline containing a porous vermiculite-containing silica gel mesoporous composite material prepared by the present invention.

[0081] (1) Preparation of porous vermiculite-containing silica gel mesoporous composite materials

[0082] 0.002 mol of triblock copolymer P123, 0.001 mol of triblock copolymer F127 and 0.6 mol of ethanol were added to 300 mL of a buffer solution of acetic acid and sodium acetate (pH = 4.4), and stirred at 20°C until P123 was completely dissolved. Then, 0.52 mol of trimethylpentane was added to the above solution, and stirred at 20°C for 6 hours. Then, 0.2 mol of tetramethoxysilane was added to the above solution, and stirred at 20°C for 20 hours. The solution was transferred to a polytetrafluoroethylene-lined reactor, and crystallized at 60°C for 24 hours, filtered, washed with distilled water, and a mesoporous molecular sieve filter cake 1 was obtained.

[0083] 0.35 mol of hexadecyltrimethylammonium bromide and 1.0 mol of ethyl orthosilicate were added to a 25% ammonia solution containing 3.0 mol of ammonia water, and diluted with 2880 g of deionized water. The mixture was stirred at 30°C until dissolved, and continued to be stirred at 30°C for 3 hours. The solution was filtered to obtain a mesoporous material filter cake, and the filter cake was washed to a pH of 7 to obtain a mesoporous molecular sieve filter cake 2.

[0084] Water glass with a concentration of 15 weight percent, sulfuric acid solution with a concentration of 12 weight percent and n-butanol were mixed in a weight ratio of 5:1:1 and contacted and reacted at 30° C. for 2 hours, and then the pH value was adjusted to 3 with sulfuric acid with a concentration of 98 weight percent. The obtained reaction material was then filtered and washed with distilled water until the sodium ion content was less than 0.02 weight percent to obtain a silica gel filter cake.

[0085] 5 grams of mesoporous molecular sieve filter cake 1, 5 grams of mesoporous molecular sieve filter cake 2, 10 grams of vermiculite powder, and 10 grams of silica gel filter cake prepared above were put into a 100mL ball mill and sealed. Among them, the ball mill is made of agate, the grinding ball is made of agate, the diameter of the grinding ball is 3mm, the number is 1, and the rotation speed is 400r / min. After ball milling at 60℃ for 3 hours, a solid powder was obtained. The solid powder was dissolved in 30 grams of deionized water and spray-dried at 200℃ and a rotation speed of 12000r / min; the product obtained after spray drying was calcined at 500℃ in a muffle furnace for 24 hours to remove the template agent, and a porous vermiculite-containing silica gel mesoporous composite material A was obtained. The structural parameters of the porous vermiculite-containing silica gel mesoporous composite material A are listed in Table 1.

[0086] Figure 1 is the X-ray diffraction spectrum of the porous vermiculite-containing silica gel mesoporous composite material A, wherein the abscissa is 2θ (°) and the ordinate is intensity; Figure 1 It can be seen that the porous vermiculite-containing silica gel mesoporous composite material A has a 2D hexagonal pore structure that is unique to mesoporous materials.

[0087] Figure 2 This is the SEM scanning electron microscope image of the porous vermiculite-containing silica gel mesoporous composite material A. Figure 2 It can be seen that the microscopic morphology of the porous vermiculite-containing silica gel mesoporous composite material A is mesoporous spheres with a particle size of 20-60 μm.

[0088] (2) Preparation of catalyst for increasing propylene production by cracking of light gasoline

[0089] 27g of the porous vermiculite-containing silica gel mesoporous composite material A prepared in the above steps was mixed evenly with 54g of ZSM-5 molecular sieve with SiO2 / Al2O3 of 300, 20g of pseudo-boehmite with a water content of 30% and 6g of sesbania powder, and then 70mL of 5% dilute nitric acid was added, stirred evenly and extruded; dried at 110°C for 10 hours, and finally calcined at 550°C for 8 hours to obtain catalyst precursor A. 95g of catalyst precursor A was impregnated with 100mL of an aqueous solution containing calcium nitrate, cerium nitrate and phosphoric acid, dried at 110°C for 16 hours, and calcined at 580°C for 8 hours to obtain catalyst A.

[0090] The composition of Catalyst A is listed in Table 2.

[0091] (3) Catalyst performance test

[0092] The performance of the light gasoline catalytic cracking reaction of catalyst A was evaluated in a fixed bed reactor. The reaction raw materials were: C5-C8 light gasoline raw material composition: normal alkanes 7.71, isoalkanes 40.49, olefins 51.46, cycloalkanes 0.36. The loading amount of catalyst A was 5.0 g, the reaction temperature was 540 ° C, the reaction pressure was 0.05 MPa, and the raw material weight space velocity was 16 h -1 After the product was cooled and separated from the gas and liquid, the gas composition was analyzed by an Agilent 6890 gas chromatograph equipped with an Al2O3-S capillary column and a hydrogen flame detector (FID), and the quantitative analysis was performed by temperature program and correction factor; the liquid composition was analyzed by an Agilent 6890 gas chromatograph equipped with a PONA column, and the quantitative analysis was performed by temperature program and light gasoline standard. The reaction results are shown in Table 3.

[0093] Example 2-3

[0094] This example is intended to illustrate the catalyst for increasing propylene production by cracking light gasoline containing a porous vermiculite-containing silica gel mesoporous composite material prepared by the present invention.

[0095] Example 2 and Example 3 were carried out in the same manner as step (1) and step (2) in Example 1, except that the components, amounts of the components and preparation conditions in the preparation process of the porous vermiculite-containing silica gel mesoporous composite material in step (1) and the preparation process of the catalyst in step (2) were changed, as shown in Table 1, to obtain porous vermiculite-containing silica gel mesoporous composite materials B and C, and catalyst B and catalyst C, respectively.

[0096] Table 1 lists the components, amounts of the components and preparation conditions in the preparation process of porous vermiculite-containing silica gel mesoporous composite materials B and C, as well as the structural parameters of the prepared porous vermiculite-containing silica gel mesoporous composite materials B and C.

[0097] Table 2 lists the compositions of Catalysts B and C.

[0098] The performance of catalysts B and C was evaluated in the same manner as step (3) in Example 1. The test results are listed in Table 3.

[0099] Example 4

[0100] This example is intended to illustrate the catalyst for increasing propylene production by cracking light gasoline containing a porous vermiculite-containing silica gel mesoporous composite material prepared by the present invention.

[0101] Catalyst D was prepared in the same manner as in Example 1, except that the amounts of the porous vermiculite-containing silica gel mesoporous composite material A, ZSM-5 molecular sieve, pseudo-boehmite, sesbania powder, dilute nitric acid, and an aqueous solution containing calcium nitrate, cerium nitrate, and phosphoric acid were changed, and the "aqueous solution containing calcium nitrate, cerium nitrate, and phosphoric acid" was replaced with "an aqueous solution containing calcium nitrate, lanthanum nitrate, and boric acid";

[0102] The results showed that, based on the total weight of the catalyst D, the content of ZSM-5 zeolite molecular sieve was 63% by weight, the content of porous vermiculite silica gel mesoporous composite material A was 15% by weight, the content of aluminum oxide from the binder was 20% by weight, the content of calcium oxide was 0.5% by weight, the content of lanthanum oxide was 1.1% by weight, and the content of boron trioxide was 0.4% by weight.

[0103] The performance of Catalyst D was evaluated in the same manner as step (3) in Example 1. The test results are listed in Table 3.

[0104] Comparative Example 1

[0105] Catalyst D1 was prepared in the same manner as in Example 1, except that step (1) was omitted, and in step (2), the porous vermiculite-containing silica gel mesoporous composite material A was not used, and only 160 g of ZSM-5 molecular sieve with a SiO2 / Al2O3 ratio of 300 was used; and the amounts of the various components and the modified oxide precursor were changed. The results are shown in Table 2.

[0106] The performance of catalyst D1 was evaluated in the same manner as step (3) in Example 1. The test results are listed in Table 3.

[0107] Comparative Example 2

[0108] Catalyst D2 was prepared in the same manner as in Example 1, except that step (1) was eliminated, and in step (2) "50 g of porous vermiculite-containing silica gel mesoporous composite material A" was replaced by "50 g of commercially available silica"; and the amounts of each component and the modified oxide precursor were changed. The results are shown in Table 2.

[0109] The performance of catalyst D2 was evaluated in the same manner as step (3) in Example 1. The test results are listed in Table 3.

[0110] Comparative Example 3

[0111] Catalyst D3 was prepared in the same manner as in Example 1, except that the "high silicon-aluminum ratio ZSM-5 zeolite molecular sieve (SiO2 / Al2O3 is 300)" in step (1) was replaced by "low silicon-aluminum ratio ZSM-5 zeolite molecular sieve (SiO2 / Al2O3 is 50)".

[0112] The performance of catalyst D3 was evaluated in the same manner as step (3) in Example 1. The test results are listed in Table 3.

[0113] Comparative Example 4

[0114] Catalyst D4 was prepared in the same manner as in Example 1, except that the amounts of the porous vermiculite-containing silica gel mesoporous composite material A, ZSM-5 molecular sieve, pseudo-boehmite, sesbania powder, dilute nitric acid, and an aqueous solution containing calcium nitrate, cerium nitrate, and phosphoric acid were changed, and the "aqueous solution containing calcium nitrate, cerium nitrate, and phosphoric acid" was replaced with "an aqueous solution containing calcium nitrate, lanthanum nitrate, and phosphoric acid".

[0115] The results showed that, based on the total weight of the catalyst D4, the content of ZSM-5 zeolite molecular sieve was 73 weight %, the content of porous vermiculite silica gel mesoporous composite material A was 7 weight %, the content of aluminum oxide from the binder was 7 weight %, the content of calcium oxide was 5.1 weight %, the content of lanthanum oxide was 4.3 weight %, and the content of phosphorus pentoxide was 3.6 weight %.

[0116] The performance of catalyst D4 was evaluated in the same manner as step (3) in Example 1. The test results are listed in Table 3.

[0117] Table 1

[0118]

[0119]

[0120] Table 2

[0121]

[0122]

[0123] Table 3

[0124]

[0125] It can be seen from Table 3 that the catalyst provided by the present invention has excellent performance when used for the catalytic cracking of light gasoline to produce propylene. Comparing the data of catalyst A and catalysts D1 and D2, it can be seen that a part of the porous vermiculite-containing silica gel mesoporous composite material is added to catalyst A, and the porous vermiculite-containing silica gel mesoporous composite material is not added to catalysts D1 and D2. Compared with catalysts D1 and D2, the light gasoline olefin conversion rate, propylene selectivity and catalyst stability of catalyst A are significantly improved. The above results show that the reason why the light gasoline cracking and propylene production increasing catalyst provided by the present invention has excellent performance is that it contains an appropriate amount of porous vermiculite-containing silica gel mesoporous composite material.

[0126] Comparing the data of catalyst A and catalyst D3, it can be seen that the performance of the catalyst for increasing propylene production by cracking light gasoline prepared using hydrogen-type ZSM-5 molecular sieve with a relatively low silicon-aluminum ratio is poor. Although the olefin conversion rate in light gasoline is high at the beginning of the reaction, the propylene selectivity is low. In addition, as the reaction proceeds, the conversion rate and selectivity of catalyst D3 decrease significantly, while catalyst A maintains stable performance throughout the 100h reaction process. And due to the introduction of vermiculite, the extension of reaction time is more conducive to the improvement of light gasoline olefin conversion rate and propylene selectivity.

[0127] Comparing the data of catalyst A and catalyst D4, it can be seen that if the content of zeolite molecular sieve is too high, the content of porous vermiculite silica gel mesoporous composite material is too low, the content of bonding oxide is too low, and the content of modified oxide is too high, the conversion rate and selectivity of catalyst D4 are significantly reduced.

[0128] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalyst for increasing propylene production by cracking light gasoline, characterized in that: The catalyst for increasing propylene production by cracking light gasoline comprises a zeolite molecular sieve, a porous vermiculite-containing silica gel mesoporous composite material, a bonding oxide and a modified oxide, and based on the total weight of the catalyst for increasing propylene production by cracking light gasoline, the content of the zeolite molecular sieve is 45-65% by weight, the content of the porous vermiculite-containing silica gel mesoporous composite material is 15-35% by weight, the content of the bonding oxide is 10-20% by weight, and the content of the modified oxide is 1-9% by weight; The average particle size of the porous vermiculite-containing silica gel mesoporous composite material is 20-60 μm, and the specific surface area is 100-800 m 2 / g, the pore volume is 1-2mL / g, the pore size presents a four-peak distribution, and the first most probable pore size corresponding to the four peaks is 1-2nm, the second most probable pore size is 2-3nm, the third most probable pore size is 3-5nm, and the fourth most probable pore size is 20-40nm.

2. The catalyst for increasing propylene production by cracking light gasoline according to claim 1, wherein: The specific surface area of ​​the porous vermiculite-containing silica gel mesoporous composite material is 100-200m 2 / g, the pore volume is 1.4-1.8mL / g, the pore size presents a four-peak distribution, and the first most probable pore size corresponding to the four peaks is 1.2-1.9nm, the second most probable pore size is 2.6-2.7nm, the third most probable pore size is 3.5-3.9nm, and the fourth most probable pore size is 31-37nm.

3. The catalyst for increasing propylene production by cracking light gasoline according to claim 1, wherein: Based on the total weight of the light gasoline cracking and propylene production increasing catalyst, the content of the zeolite molecular sieve is 51-58 weight %, the content of the porous vermiculite-containing silica gel mesoporous composite material is 23-28 weight %, the content of the bonding oxide is 11-19 weight %, and the content of the modified oxide is 3-7 weight %.

4. The catalyst for increasing propylene production by cracking light gasoline according to claim 1 or 3, wherein: The zeolite molecular sieve is a hydrogen-type high-silicon ZSM-5 molecular sieve; Preferably, the SiO2 / Al2O3 molar ratio of the hydrogen-type high-silicon ZSM-5 molecular sieve is 100-800, more preferably 200-500; Preferably, the weight ratio of the hydrogen-type high-silicon ZSM-5 molecular sieve to the porous vermiculite-containing silica gel mesoporous composite material is (1.5-4.5):

1.

5. The catalyst for increasing propylene production by cracking light gasoline according to any one of claims 1 to 4, wherein: The bonding oxide is a product of a calcined bonding agent, preferably silicon oxide and / or aluminum oxide; Preferably, the binder is selected from one or more of silica sol, alumina sol, pseudo-boehmite and diaspore.

6. The catalyst for increasing propylene production by cracking light gasoline according to any one of claims 1 to 4, wherein: The modified oxide is selected from one or more of magnesium oxide, calcium oxide, strontium oxide, barium oxide, zinc oxide, boron oxide, cerium oxide, lanthanum oxide, zirconium dioxide and phosphorus-containing oxides.

7. The catalyst for increasing propylene production by cracking light gasoline according to any one of claims 1 to 4, wherein: The preparation method of the porous vermiculite-containing silica gel mesoporous composite material comprises: (a) in the presence of a first template, a second template, trimethylpentane and ethanol, tetramethoxysilane is first contacted with an acidic aqueous solution, and the mixture after the first contact is crystallized, washed and filtered to obtain a mesoporous molecular sieve filter cake 1; (b) subjecting the third template, tetraethyl orthosilicate and ammonia water to a second contact, and subjecting the mixture after the second contact to crystallization and filtering to obtain a mesoporous molecular sieve filter cake 2; (c) contacting water glass, an inorganic acid and n-butanol for a third time, and filtering the mixture after the third contact to obtain a silica gel filter cake; (d) The mesoporous molecular sieve material filter cake 1, the mesoporous molecular sieve material filter cake 2, vermiculite, and the silica gel filter cake are mixed and ball-milled, and the solid powder after the ball milling is slurried with water to obtain a slurry, and the slurry is spray-dried and calcined to obtain a porous vermiculite-containing silica gel mesoporous composite material.

8. The catalyst for increasing propylene production by cracking light gasoline according to claim 7, wherein: In step (a), the first template and the second template are both triblock copolymers of polyethylene oxide-polypropylene oxide-polyethylene oxide; Preferably, the first template is P123, with the molecular formula EO 20 PO 70 EO 20 The second template is F127, with a molecular formula of EO 106 PO 70 EO 106 ; Preferably, the molar ratio of the first template, the second template, ethanol, the acidic aqueous solution, trimethylpentane and tetramethoxysilane is 1: (0.1-2): (100-500): (150-900): (200-500): (50-200), preferably 1: (0.2-1): (200-400): (300-600): (250-400): (70-150); Preferably, the conditions for the first contact include: temperature of 10-40°C and time of 10-48h.

9. The catalyst for increasing propylene production by cracking light gasoline according to claim 7, wherein: In step (b), the third template is hexadecyltrimethylammonium bromide; Preferably, the molar ratio of the tetraethyl orthosilicate, the third template, the ammonia in the ammonia water and the water in the ammonia water is 1: (0.1-1): (0.1-5): (100-200), preferably 1: (0.2-0.5): (1.5-3.5): (120-180); Preferably, the conditions for the second contact include: temperature of 10-60° C. and time of 1-5 h.

10. The catalyst for increasing propylene production by cracking light gasoline according to claim 7, wherein: In step (c), the inorganic acid is selected from one or more of sulfuric acid, nitric acid and hydrochloric acid; Preferably, the weight ratio of the inorganic acid: n-butanol: water glass is 1: (0.5-2): (3-6); Preferably, the third contact conditions include: temperature of 10-60° C., time of 1-5 h, and pH of 2-4.

11. The catalyst for increasing propylene production by cracking light gasoline according to claim 7, wherein: In step (d), based on 100 parts by weight of the mesoporous molecular sieve filter cake 1, the amount of the mesoporous molecular sieve filter cake 2 is 20-300 parts by weight, preferably 50-200 parts by weight; the amount of the silica gel filter cake is 50-500 parts by weight, preferably 100-300 parts by weight; the amount of the vermiculite is 50-500 parts by weight, preferably 100-300 parts by weight; Preferably, the calcination conditions include: a temperature of 400-600° C. and a time of 10-60 h.

12. A method for preparing the catalyst for increasing propylene production by cracking light gasoline according to any one of claims 1 to 11, characterized in that: The preparation method comprises: (1) in the presence of dilute nitric acid, mixing a zeolite molecular sieve, a porous vermiculite-containing silica gel mesoporous composite material, a binder and an extrusion aid, extruding and performing a first calcination treatment to obtain a catalyst precursor; (2) The catalyst precursor is immersed in an aqueous solution of a modified oxide precursor and then dried and subjected to a second calcination treatment to obtain a catalyst for increasing propylene production by cracking light gasoline.

13. The preparation method according to claim 12, wherein: In step (1), relative to 500 mL of dilute nitric acid, the amount of the zeolite molecular sieve is 1000-1400 parts by weight, the amount of the porous vermiculite-containing silica gel mesoporous composite material is 400-600 parts by weight, the amount of the binder is 300-500 parts by weight, and the amount of the extrusion aid is 100-300 parts by weight; Preferably, in step (2), relative to 100 mL of water, the amount of the catalyst precursor is 70-100 parts by weight, and the amount of the oxide precursor is 10-30 parts by weight.

14. The preparation method according to claim 12, wherein: The modified oxide precursor includes an inorganic salt of a metal and / or an inorganic acid of a non-metal; Preferably, the metal is selected from one or more of magnesium, calcium, strontium, barium, zinc, cerium, lanthanum and zirconium, and the non-metal is boron and / or phosphorus; Preferably, the extrusion aid is selected from one or more of sesbania powder, cellulose, polyethylene glycol, polyvinyl alcohol and starch, more preferably sesbania powder and / or polyethylene glycol.

15. The preparation method according to claim 12, wherein: In step (1), the first calcination conditions include: temperature of 500-600°C and time of 3-20h; Preferably, in step (2), the conditions for the second calcination include: a temperature of 500-600° C. and a time of 4-10 h.

16. Use of the catalyst for increasing propylene production by cracking light gasoline as claimed in any one of claims 1 to 11 in catalytic cracking.

Citation Information

Patent Citations

  • Composited HZSM-5 zeolite / vermiculite catalyst and its usage

    CN1059673A

  • Light gasoline cracking yield-increasing propylene catalyst containing spherical chlorite mesoporous composite material, and preparation method and application thereof

    CN113318781A

  • Method for preparing propylene catalyst by adopting sepiolite mesoporous composite material, propylene catalyst and method for preparing propylene by cracking MTBE (Methyl Tert-Butyl Ether)

    CN114425434A

  • Light gasoline cracking yield-increasing propylene catalyst containing porous aluminum-containing silica gel mesoporous composite material as well as preparation method and application of light gasoline cracking yield-increasing propylene catalyst

    CN114515594A

  • Process for reacting alcohols and olefins

    US4496785A